90 Falls Efficacy Related Instruments for Community-Dwellig Older Adults – Development and Content Validity: A Cosmin-Based Systematic Review. (20th December 2019) - Soh, Shawn Leng-Hsien; Tan, Chee-Wee; Judith, Lane; Gleeson, Nigel; Xu, Tim
Abstract: Background: Falls efficacy is a widely-studied latent construct in community-dwelling older adults. Various self-reported instruments have been used to measure falls efficacy. Empirical evidence is needed to justify the selection of a specific instrument to measure the intended construct. Objectives: To summarize evidence on the development, content validity and structural validity of instruments measuring falls efficacy in community-dwelling older adults using Consensus-based Standards for the Selection of Health Measurement Instruments (COSMIN) checklist. Study Design and Setting: MEDLINE, Web of Science, PsychINFO, SCOPUS, CINAHL were searched (May 2019). Records on development of instruments and studies assessing content validity or structural validity of falls efficacy related scales were included. COSMIN methodology guided the review of eligible studies and methodological quality. Evidence of content validity: relevance, comprehensiveness and comprehensibility and unidimensionality for structural validity were synthesized. A modified GRADE approach was applied to evidence synthesis. Results: 35 studies on 18 instruments were included in the review. High quality evidence showed that modified Falls-Efficacy Scale (FES)–13 items (mFES-13) is relevant but not comprehensive for measuring falls efficacy. Moderate quality evidence supported the FES-10 had sufficient relevance and the mFES-14 had sufficient comprehensibility. Only the Activities-specific Balance Confidence (ABC) Scale–Simplified (ABC-15) had sufficient relevance of moderate quality evidence to measure balance confidence. Low to very low quality evidence underpinned content validity of other instruments. High quality evidence supported sufficient unidimensionality for eight instruments (FES-10, mFES-14, ABC-6, ABC-15, ABC-16, Iconographical FES (Icon-FES), FES–International (FES-I) and Perceived Ability to Prevent and Manage Fall Risks (PAPMFR)). Conclusion: Content validity of the instruments to measure falls efficacy is understudied. Structural validity is sufficient for a number of widely-used instruments. Measuring balance confidence is a subset of falls efficacy. Further work is needed to investigate the broader continuum of falls efficacy.